TINJAUAN VICTIMOLOGI TERHADAP ANAK PENYANDANG DISABILITAS KORBAN TINDAK PIDANA PELECEHAN SEKSUAL - ainun, Nur; Asmara, Romi; Johari, Johari (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
This research aims to find out how to provide legal protection from a victimology perspective and also from the types of rights and facilities for children with disabilities by fulfilling the requirements of the law regarding sexual violence against children by having protection from the witness and victim protection agency (LPSK) and the commission. child protection (KPAI) in providing protection to children with disabilities in Indonesia. This research uses a normative juridical legal research method which uses secondary data sources collected which are descriptive in nature. The result of this research is to provide legal protection from a victimology perspective and also from the types of rights and facilities for children with disabilities by fulfilling the requirements of the law regarding sexual violence against children by having protection from the witness and victim protection agency (LPSK) and the commission. child protection (KPAI) in providing protection to children with disabilities in Indonesia, as well as paying attention to the human rights of children with disabilities. Keywords: Legal Protection, Rights to Facilities, Children with Disabilities